Penerapan Nilai-Nilai Keislaman Pada Masyarakat Islam Minoritas Desa Lau Buluh Kecamatan Kuta Buluh Kabupaten Karo - Saputra, A. (AL-HIKMAH:Jurnal Theosofi dan Peradaban Islam, 2023)
This study aims to describe the social conditions and the application of Islamic values in the Muslim community in Lau Buluh Village, Kec. Kuta Buluh Kab. Karo as a community group belonging to the minority. So this research is a qualitative research type of field study using a descriptive approach. Primary data in this study were obtained directly through interviews. While the secondary data in this study were obtained through a literature review. Data collection techniques in this study used participatory observation techniques, semi-structured interview techniques, and documentation /literature. The data analysis technique used in this study is data analysis using the Miles and Huberman model, with activities in data analysis starting from data collection, data reduction, data presentation, and drawing conclusions/verification. The results of this study revealed that; 1) The social condition of the Islamic community in Lau Buluh Village failed to actualize ukhuwah Islamiyah. The reason is because each individual community has a different education, character and different backgrounds. Moreover, religious leaders have not made maximum efforts to establish cooperation with related parties to build ukhuwah Islamiyah. On the other hand, the lack of intensity in the relationship between religious leaders and other parties is recognized as a form of disappointment and pessimism in the face of uncooperative public responses. 2) The application of Islamic values to the Islamic community in Lau Buluh Village is only limited to: Friday prayers in congregation; wirid yasin on Friday night; commemoration of Islamic holidays; donate and give charity. Thus, through the application of Islamic values to the Lau Buluh community, the community belongs to a society that has a symbolic normative understanding of Islam.Keywords: Application, Islamic Values, Minority.